A Guide to Using the Computer in the Writing Process - Wisconsin Univ., Madison. Dept. of Curriculum and Instruction; Christensen, Linda; Wisconsin Univ., Madison. Dept. of Curriculum and Instruction ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Intended for use by both elementary and secondary school teachers, this booklet is designed to answer questions instructors might have as they consider integrating microcomputers into their writing programs. Following a brief introductory section, the second section of the booklet reviews the advantages and disadvantages of using computers in the writing class. Disadvantages discussed include lack of teacher and student access to computers, staff resistance, lack of funding, lack of good programs, and the depersonalization of instruction. Advantages discussed include student motivation, the stimulation of ideas, prompt feedback, and the possibility of individualized instruction. The third section examines essentials in preparing both students and teachers to use computers, and the fourth reviews classroom management considerations, such as scheduling. The fifth, and most extensive section, discusses software evaluation, lists sources that provide evaluations, and sets forth evaluation criteria. In addition, this section provides a software evaluation form and uses the form to evaluate a number of programs. The sixth section discusses the uses of word processors and text editors in the writing process, reviewing research that shows the advantages and disadvantages of the word processors in revision. (FL)
Availability: Wisconsin Writing Project, 556c Teacher Education Building, University of Wisconsin, 225 North Mills St., Madison, WI 53706 ($2.50).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Class Activities; Computer Assisted Instruction; Computer Software; Elementary Secondary Education; Evaluation Criteria; Microcomputers; Teacher Role; Teaching Methods; Word Processing; Writing Instruction; Writing Processes; Wisconsin Writing Project; National Writing Project; Guides, Classroom -- Teacher; Opinion Papers